Great moderations and US interest rates: Unconditional evidence - James M. Nason; Gregor W. Smith (Federal Reserve Bank of Atlanta, 2008)
The Great Moderation refers to the fall in U.S. output growth volatility in the mid-1980s. At the same time, the United States experienced a moderation in inflation and lower average inflation. Using annual data since 1890, we find that an earlier 1946 moderation in output and consumption growth was comparable to that of 1984. To assess the impact of these moderations, we also isolate the 1969-83 Great Inflation using quarterly data since 1947. We then examine the quantitative predictions of a consumption-based asset pricing model for shifts in the unconditional average of U.S. interest rates across these time periods. A central finding is that such shifts probably were related to changes in average inflation rather than to moderations in inflation and consumption growth.
Keywords: E32; E43; N12; 330; Great Moderation; asset pricing; interest rate